THE DESCRIPTION OF HISTOPATHOLOGY IN BREAST CANCER PATIENTS AT RSUP.H. ADAM MALIK MEDAN - Siregar, Ice Ratnalela (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2018)
Breasts are an important organ for women. Breasts can experience various disorders or diseases, bothserious and mild disease. Among these are breast cancer which is one of the most dreaded breastabnormalities. Breast cancer is a cancer that comes from the gland, glandular, and breast supporttissue.Breast cancer has been known to attack only women. In fact, malignant tumors are also biased alsoagainst men. The histopathologic feature is a diagnostic feature of breast cancer. The purpose of this studywas to determine the histopathologic description of Breast Cancer at RSUP.H.Adam Malik. The sample inthis study is all breast cancer patients who have been diagnosed by doctors who visit the RSUP.H.AdamMalik (Population). The research method used is descriptive of taking secondary data in medical record atRSU.H.Adam Malik. The results of this study can be seen that of 60 breast cancer patients who do biopsy,the majority of patients have histopathology of breast cancer invasive Ductal Carcinoma as much as 31people (51.66%) and Invasive Breast Cancer Nos Type of 29 people (48.34%).